Helen Morales, Vision and Narrative in Achilles Tatius’ Leucippe and Clitophon, Cambridge University Press, 2004, 270 pp. ISBN 0-521-64264-7 (Minerva. Revista de Filología Clásica, 2019)
Reseña de Helen Morales, Vision and Narrative in Achilles Tatius’ Leucippe and Clitophon, Cambridge University Press, 2004, 270 pp. ISBN 0-521-64264-7